Pengaruh Penggunaan Metode Discussion Group terhadap Motivasi dan Hasil Belajar Siswa pada Pembelajaran IPS Kelas VIII di MTs Darussalam Kademangan - Hayyina Winda Tsaniya; Anggoro Putranto (Journal on Education, 2024)
This research is motivated by the low motivation and learning outcomes of students in Social Studies. This issue arises because the teaching process is heavily dominated by the teacher, resulting in low student motivation and learning outcomes. Therefore, a teaching method is needed that provides students with the opportunity to construct their own knowledge, one of which is the Discussion Group Method. This method is developed to train students in questioning and answering skills. The Discussion Group Method is very effective for involving students in reviewing the material that has been taught. The research approach used is a quantitative approach with an experimental research type. The population in this study consists of eighth grade students at MTs Darussalam Kademangan. The sample used is 52 students, selected using Purposive Sampling technique. Data collection techniques in the study include questionnaires and tests. To measure both variables, validity and reliability tests of the instruments were conducted, along with prerequisite tests using normality and homogeneity tests, and hypothesis testing using the t-test. The results of the study conducted at MTs Darussalam Kademangan from April 25 to 30, 2024, are as follows: (1) There is a significant influence of the Discussion Group Method on learning motivation. This is evidenced by the t-test results with a Sig. (2-tailed) value of 0.001. Based on the decision-making criteria of 0.001 < 0.05, Ho is rejected and Ha is accepted. (2) There is a significant influence of the Discussion Group Method on learning outcomes. This is evidenced by the t-test results with a Sig. (2-tailed) value of 0.000. Based on the decision-making criteria of 0.000 < 0.05, Ho is rejected and Ha is accepted. Keywords: Discussion Group Method, Learning Motivation, Learning Outcomes